Rancang Bangun Aplikasi Web Tetok: Sistem Penjualan Mandiri dan Kasir dengan Pembayaran Digital dan Integrasi Barcode Scanner - Rizki Iqbal Muladi Rizki Iqbal; Yoki Muchsam; Farhan Hamdallah (Universitas Sains Indonesia Publishing, 2026)
The accelerating digital economy pushes micro and small retailers to move from manual cashiers to compact, accurate, cashless-ready solutions. The urgency is evident: pricing entry mistakes, and slow reconciliation erode customer experience and margins. This research focuses on the development and implementation of TETOK, a self-service sales and cashier application integrating digital payments and barcode scanning to reduce transaction friction. The methodology covers stakeholder requirement analysis, system design using UML, web/mobile modular implementation, and black-box testing combined with usability evaluation. The application provides instant barcode capture, product catalog, automatic cart, computed discounts and taxes, QRIS/e-wallet options, and a dashboard summarizing daily sales. Experiments in small retail scenarios show TETOK accelerates checkout by up to forty percent versus manual cashiering, reduces recording errors, and improves stock visibility. The impact includes higher operational efficiency, shorter customer waiting times, and real-time sales data for decision-making. The design also enables future integrations, such as accounting synchronization and multi-branch inventory, while encouraging secure, standardized digital payment adoption. TETOK demonstrates that a focused self-service approach, paired with barcode scanning and digital payments, can deliver a fast, low-contact, end-to-end auditable shopping experience. Implementation proved flexible, easy for staff to learn, cost-effective to operate, and readily scalable nationwide.